Benefits of SQ4R Method in Reading Comprehension to Improve Student Literacy - Fadillah, Rifky; Raihanzaki, Raka Gading; Shofiyani, Zulfatun (Universitas Wijaya Kusuma Surabaya, 2024)
Understanding reading using the SQ4R method is one way to foster a reading culture and increase student literacy levels. Literacy culture must be developed to improve the literacy level of the community, especially students. By increasing literacy, one's expertise and knowledge can be implemented with creativity and innovation. Purpose Research. This article aims to discover the benefits of applying the SQ4R method in understanding reading to improve student skills and knowledge. Methods. The method used in this article is library research. Result. The results of the implementation of the SQ4R method in understanding reading are helpful for students in higher education, and this can be seen from the skill and knowledge of more developed students and experts in the fields studied so that student literacy skills can increase and students can be creative and produce innovation in their scientific fields.Keyword: Literacy, SQ4R method, Understanding readings